An Examination of Business Performance: The Relationship and Its Relevance Factors - Hanafi, Hanafi; Pornomo, Harry; Norhidayat, Norhidayat; Maharani, Anita (Universitas Muhammadiyah Jakarta, 2023)
Within the purview of influencing factors, due consideration is given to the adoption of technology and the role played by external assistance. Moreover, this study underscores the crucial function of business continuity as a mediating factor in this intricate equation and the moderating influence of employee creativity. The primary objective of this research is to delve into the multifaceted elements that exert influence on the overall success of small and medium businesses (SMEs). Employing a rigorous quantitative research approach, a carefully selected cohort of 109 respondents was drawn from the SME community. These respondents were sourced from the membership pool of a financial counseling group affiliated with PT. TASPEN (PERSERO), providing a comprehensive cross-section of perspectives and experiences. The insightful findings derived from this study corroborate the hypothesis that external assistance can indeed have a constructive impact on company performance. However, this influence is found to be channeled through the mediating role of SME business continuity, thus underscoring the importance of maintaining operational resilience and consistency. The research did not find conclusive evidence supporting a direct link between technological adoption and business success within the SME context, indicating that further investigation might be warranted to elucidate this relationship. Nonetheless, these findings provide valuable insights into the intricate web of factors influencing SME success and offer pertinent guidance for businesses aiming to thrive in an ever-evolving landscape.